Additive Manufacturing Cloud via Peer-Robot Collaboration. (20th May 2016) - Yao, Yuan; Chen, Dong; Wang, Lei; Yang, Xiaoming
When building a 3D printing cloud manufacturing platform, self-sensing and collaboration on manufacturing resources present challenging problems. This paper proposes a peer-robot collaboration framework to deal with these issues. Each robot combines heterogeneous additive manufacturing hardware and software, acting as an intelligent agent. Through collaboration with other robots, it forms a dynamic and scalable integration manufacturing system. The entire distributed system is managed by rules that employ an internal rule engine, which supports rule conversion and conflict resolution. Two additive manufacturing service scenarios are designed to analyse the efficiency and scalability of the framework. Experiments show that the presented method performs well in tasks requiring large-scale access to resources and collaboration.